Implementation of a PBL Model Based on a Process Differentiation Approach to Improve High School Students’ Problem-Solving Skills in the Topic of Static Fluids - Karimah Fajriani; Lina Aviyanti; Winny Liliawati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Problem-solving skills are considered essential competencies in 21st-century physics education, yet many students experience difficulties in solving physics problems effectively. This study aimed to examine the effectiveness of applying a Problem-Based Learning (PBL) model integrated with a process differentiation approach in enhancing senior high school students’ problem-solving skills on the topic of static fluids. The study employed a quantitative quasi-experimental design with a nonequivalent control group format. Participants consisted of 68 eleventh-grade students from a public senior high school in Bandung, divided into an experimental group and a control group. In the experimental class, process differentiation was implemented through varied learning activities tailored to students’ learning-style characteristics. Data were gathered through essay-based tests designed to measure problem-solving skills and were analyzed using N-Gain and Mann–Whitney tests. The findings revealed that students in the experimental class showed greater improvement, with an average N-Gain score of 0.51, compared to 0.31 in the control class. In addition, the calculated Cohen’s d value of 1.1 indicated a strong practical effect of the treatment. The results suggest that integrating process differentiation into the PBL model effectively improves students’ problem-solving skills in learning about static fluids. The findings contribute to the growing body of evidence supporting the integration of differentiated instruction with Problem-Based Learning as an effective pedagogical approach for physics education.